2007
DOI: 10.1002/eat.20491
|View full text |Cite
|
Sign up to set email alerts
|

Geographical clustering of eating disordered behaviors in U.S. high school students

Abstract: The significant clustering of weight control and eating disorder behavior in U.S. high school students confirms evidence of a social contagion effect of eating disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…These results are supported by several previous studies which have demonstrated similar social contagion effects [13][14][15][16][17][18][19][20]32], but contribute to existing literature in important ways. By using a 5-year longitudinal dataset and adjusting analyses for use of disordered eating behavior at baseline, we were able to examine change in these behaviors across adolescence, which has not been done previously.…”
Section: Discussionsupporting
confidence: 84%
“…These results are supported by several previous studies which have demonstrated similar social contagion effects [13][14][15][16][17][18][19][20]32], but contribute to existing literature in important ways. By using a 5-year longitudinal dataset and adjusting analyses for use of disordered eating behavior at baseline, we were able to examine change in these behaviors across adolescence, which has not been done previously.…”
Section: Discussionsupporting
confidence: 84%
“…It will also be important to identify the shared environmental factors (i.e., experiences that co-twins share and would make twins more likely to select similar peer groups) that contribute to selection. These experiences could be due to macro-level variables, such as influences within specific communities contributing to increased emphasis on the thin-ideal/disordered eating behaviors (e.g., the clustering of eating disordered behaviors within counties; see Forman-Hoffman & Cunningham, 2008). Micro shared environmental effects, such as family attitudes regarding weight/dieting (Rodgers & Chabrol, 2009), may also contribute.…”
Section: Discussionmentioning
confidence: 99%
“…38 Evidence also shows that adolescent eating disordered behaviors and adult smoking prevalence and cessation rates are impacted by the extent to which other members an individual's peer group engage in the behavior. [39][40] Contagion may also explain why the protest of the statue's removal spread from unlawful rioting and looting in the streets of Tallinn to unlawful protest online in the form of the attacks on Estonia's Internet infrastructure. There is evidence that legal violations spread not just across populations but also across types of violations.…”
mentioning
confidence: 99%